Letter from City of San Luis Obispo to San Luis Obispo Buddhist Church - J.H. Fitzpatrick (San Luis Obispo city clerk)::::::author::: (1961)
Letter from J.H. Fitzpatrick, San Luis Obispo City Clerk, to Ken Kitasako, Secretary of San Luis Obispo Buddhist Church, in response to the church's request to purchase city property to relocate the church. The church property was removed by the expansion of highway 101 in the 1960s. The city responds by stating that there is no property for sale.